2020
DOI: 10.1021/acsami.0c05554
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Intraperitoneal Aerosolization (PIPAC) and Cancer Nanomedicine: Cisplatin-Loaded Polyarginine-Hyaluronic Acid Nanocarriers Efficiently Eradicate Peritoneal Metastasis of Advanced Human Ovarian Cancer

Abstract: The UGent Institutional Repository is the electronic archiving and dissemination platform for all UGent research publications. Ghent University has implemented a mandate stipulating that all academic publications of UGent researchers should be deposited and archived in this repository. Except for items where current copyright restrictions apply, these papers are available in Open Access. This item is the archived peer-reviewed author-version of: Synergy between intraperitoneal aerosolization (PIPAC) and cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 62 publications
3
40
0
Order By: Relevance
“…The main finding of our study is that both a positive charge and the electrostatic precipitation increase the depth of tissue penetration of CUR-PLGA-NPs. Our results are in line with prior data [13,27].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The main finding of our study is that both a positive charge and the electrostatic precipitation increase the depth of tissue penetration of CUR-PLGA-NPs. Our results are in line with prior data [13,27].…”
Section: Discussionsupporting
confidence: 92%
“…Aerosolization of cisplatin-loaded polyargininehyaluronic acid nanoscale particles (Cis-pARG-HA NPs) using PIPAC efficiently eradicated peritoneal metastasis in a rat model of human ovarian cancer. At the same time, this effect was not observed for the administration of free cisplatin [27].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, one recent study demonstrated synergistic effects similar to those observed in this study with combination cisplatin-hyaluronic acid treatment in advanced metastatic ovarian cancer [19]. Another study also found that combination therapy involving hyaluronic acid exhibited synergistic and enhanced anti-tumor effects among aggressive breast cancers [20].…”
Section: Discussionsupporting
confidence: 82%
“…Experimental data suggest that formulations with prolonged intraperitoneal release administered as thermosensitive hydrogels or gelatin microspheres result in sustained (up to 14 days) exposure of residual peritoneal disease, whereas they simultaneously may prohibit formation of adhesion postoperatively [96,97]. Others have developed cisplatin-loaded polyarginine-hyaluronic acid nanoscale particles, which demonstrated increased anti-tumour efficacy when compared with free cisplatin after intraperitoneal administration in a rat model [98]. This development of new drug formulations may further improve the efficacy of HIPEC for peritoneal malignancies, such as advanced ovarian cancer, in the future.…”
Section: New Drug Formulationsmentioning
confidence: 99%